Genetic variation of some quantitative traits in ten exotic varieties of silkworm, Bombyx mori L. (University Journal of Zoology, Rajshahi University, 2012)
An investigation was conducted with ten exotic varieties of silkworm, Bombyx mori L. to estimate variability, heritability and genetic advance for nine quantitative characters. A wide range of variation was observed for the majority of the traits and a major portion of the total phenotypic variation was of genetic in nature. The maximum phenotypic and genotypic coefficient of variation was found in filament length (21.45, 21.44) and the minimum in hatching percentage (1.52, 1.44), respectively. A moderate to high heritability was recorded for these varieties. Filament length showed the highest heritability (99.98). A comparatively high heritability accompanied by a high genetic advance was also noted for majority of the traits. Substantial variability, high heritability and high genetic advance for filament length, weight of mature larvae, total number of eggs laid per female and effective rate of rearing by weight recorded in this study would afford scope for effective selection.   Key words: Bombyx mori; genetic variation; exotic varieties. DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9469 UJZRU 2010; 29(1): 65-67